2018
DOI: 10.7717/peerj.4464
|View full text |Cite
|
Sign up to set email alerts
|

Immobilized TiO2 on glass spheres applied to heterogeneous photocatalysis: photoactivity, leaching and regeneration process

Abstract: Heterogeneous photocatalysis using titanium dioxide as catalyst is an attractive advanced oxidation process due to its high chemical stability, good performance and low cost. When immobilized in a supporting material, additional benefits are achieved in the treatment. The purpose of this study was to develop a simple protocol for impregnation of TiO2-P25 on borosilicate glass spheres and evaluate its efficiency in the photocatalytic degradation using an oxidizable substrate (methylene blue), in a Compound Para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(50 citation statements)
references
References 61 publications
1
49
0
Order By: Relevance
“…In fact, the MB relative concentration gradually decreased in the run time and almost complete decolorization was achieved after 120 min of visible light irradiation. Several published papers have reported the removal of MB with fixed bed photoreactors irradiated by artificial light sources, as well as with solar photocatalytic reactors using structured photocatalysts (Table 1) [34][35][36][37][38]. For example, almost total MB decolorization was achieved after 48 h in the solar photoreactor proposed by Sutisna et al [34], in which TiO 2 nanoparticles were placed as coating on transparent granules and used in the prototype of a flat-panel photoreactor.…”
Section: Discoloration and Mineralization Of Methylene Blue With The mentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the MB relative concentration gradually decreased in the run time and almost complete decolorization was achieved after 120 min of visible light irradiation. Several published papers have reported the removal of MB with fixed bed photoreactors irradiated by artificial light sources, as well as with solar photocatalytic reactors using structured photocatalysts (Table 1) [34][35][36][37][38]. For example, almost total MB decolorization was achieved after 48 h in the solar photoreactor proposed by Sutisna et al [34], in which TiO 2 nanoparticles were placed as coating on transparent granules and used in the prototype of a flat-panel photoreactor.…”
Section: Discoloration and Mineralization Of Methylene Blue With The mentioning
confidence: 99%
“…El-Mekkawi et al [35] observed the complete decolorization after 5 h under the sunlight irradiation using a solar concentrator photoreactor prototype with TiO 2 deposited on polyethylene terephthalate (PET) textile substrate sheets. In some cases, it was reported that MB degraded more than 96% in up to 90 min of reaction using TiO 2 immobilized on glass spheres [36]. However, the same authors used a lab scale compound parabolic collector reactor irradiated by lamp at high electrical power (300 W) simulating the solar spectrum.…”
Section: Discoloration and Mineralization Of Methylene Blue With The mentioning
confidence: 99%
“…Similarly, some important processes such as waste water remediation, biofuel synthesis, and catalytic wet air oxidation reaction have also been marred by leaching of the active species. There are a few other commercially important reactions as well where leaching has been detected …”
Section: Introductionmentioning
confidence: 99%
“…Amongst various fabrications and application methods, positioning a photocatalyst near the surface of water, and on a floating support have been investigated by several researchers as it allows higher oxygenation and illumination [17,[32][33][34][35][36]. Although the initial floating supported photocatalysts were shown to be effective to clean oil slicks on water [17], the ingestion risk by fishes and animals in water and uncertain toxicity of the degradation intermediates limited their development.…”
Section: Introductionmentioning
confidence: 99%